2019
DOI: 10.1111/1460-6984.12466
|View full text |Cite
|
Sign up to set email alerts
|

Open‐class repair initiations in conversations involving middle‐aged hearing aid users with mild to moderate loss

Abstract: Background To manage conversational breakdowns, individuals with hearing loss (HL) often have to request their interlocutors to repeat or clarify. Aims To examine how middle‐aged hearing aid (HA) users manage conversational breakdowns by using open‐class repair initiations (e.g., questions such as sorry, what and huh), and whether their use of repair initiations differs from their normally hearing interlocutors. Methods & Procedures Eighteen 45–64‐year‐old adults with acquired mild to moderate HL participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Importantly, our reporting of communication breakdowns is also a robust and direct metric for assessing real-world conversational difficulty during interactive communication. Previous studies have reported that incidental noise captured during otherwise quiet recording sessions (e.g., newspaper rustling, cooking) were more likely to result in a communication breakdown [36,43,44]. Here we systemically showed the impact of increasing background noise levels on communication breakdowns during interactive communication.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Importantly, our reporting of communication breakdowns is also a robust and direct metric for assessing real-world conversational difficulty during interactive communication. Previous studies have reported that incidental noise captured during otherwise quiet recording sessions (e.g., newspaper rustling, cooking) were more likely to result in a communication breakdown [36,43,44]. Here we systemically showed the impact of increasing background noise levels on communication breakdowns during interactive communication.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, it is well documented that listeners 'let it pass' [73] to not interrupt conversational flow and rely on context to recover the intended message, and also employ nonverbal communication such as head and body movement and facial gestures (e.g., 'freeze look' [74]) to signal communication breakdown. It is also the case that our sample contained instances of communication breakdowns that transpired not because of SNR problems related to the background noise level, but rather due to the mismanagement of turn-taking (still a potential speech intelligibility problem) and/or rapid topic shifts [44,75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in their study, the interaction took place in a background of noise, whereas in the present study, the task was conducted in a quiet room. Furthermore, studies based on analysing naturally occurring conversation in everyday life have shown that non-specific requests for clarification are regularly used by people who are hard of hearing (Pajo, 2013;Laakso et al, 2019), so it is likely that their relative infrequency in the present study relates to the optimal conditions (one-to-one conversation in a quiet room) in which the testing took place.…”
Section: Discussionmentioning
confidence: 97%
“…However, Laakso et al. (2019) investigated non‐specific requests for clarification in middle‐aged adults with mild to moderate acquired hearing impairment and interlocutors without hearing impairment, finding no difference in frequency of their use between the two groups.…”
Section: Introductionmentioning
confidence: 99%